PENDAMPINGAN PROMOSI JAMU BUDHE SUM DI BEJI TIMUR DEPOK - Nuringsih, Kartika; Harry Kristanto; Kherry (Jurnal Bakti Masyarakat Indonesia, 2025)
This community service activity aims to appreciate one of the household industries in the herbal medicine field. This business is run by partners with the branding Jamu Budhe Sum in Beji Timur Village, Depok. This activity is in line with the theme of applying positive psychology to improve the quality of life of the community. Jamu as local wisdom to support community efforts to maintain health. Jamu as local wisdom to support community efforts to maintain health. Efforts to maintain the jamu business have an orientation to strengthen the psychology of jamu business actors. In running the business, in addition to earning income, it is also related to the preservation of local wisdom. This awareness is a driving force for the spirit of running a herbal business. The orientation to the herbal community is in line with sustainable development goals, especially SDGs-3 which emphasizes good health and well-being and SDGs-5 related to gender equality. This activity is carried out through promotional assistance to help increase sales. Promotion assistance was carried out to help increase sales, including getting closer to consumers from school students. The next hope is to increase sales so that it contributes to the welfare of the herbal medicine business owner. This aspect is an appreciation of gender equality in fulfilling the family economy. Public interest in drinking herbal medicine is still open so opportunities still exist. The traditional jamu market can be utilized by jamu traders as long as they have to serve jamu hygienically and innovatively according to the tastes of today's consumers including Post Gen-Z and Gen-Alpha. This appreciation strengthens the psychology for business actors to be eager to maintain herbal medicine as an economic and cultural value.